Pemberdayaan Gender, Pembangunan Gender, Belanja Pemerintah dan Pertumbuhan Ekonomi: Pendekatan Data Panel - Robiansyah, Anton; Hartono, Darwin; Tampubolon, Endy Grade; Zubir, Edwar; Sukatmi, Sri; Kharis, Selly Anastassia Amellia (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to determine the influence of gender empowerment and development as well as government expenditure on economic growth in districts/cities of East Java province in 2014-2020. The research method used is panel data regression analysis by selecting the best model between Common Effect, Fixed Effect and Random Effect with Chow test calculations. From the test results it was found that the best model was Fixed Effect. The results of data processing show that 97.70 percent of the GRDP variance is influenced by the gender empowerment index (IDG), gender development index (IPG) and government expenditure (G).